Inventaire des mouches des fruits de trois regions agroecologiques et des planteshotes associees a lespece nouvelle, Bactrocera (Bactrocera) Invadens Drew et al. (Diptera: Tephritidae) en CotedIvoire - N'Dépo, O.R.; Hala, N.F.; Gnago, A.; Allou, K.; Kouassi, K.P.; Vayssières, Jean-François; Meyer, M. de (2010)
The fruit fly Bactrocera invadens, is a frightening mango pest and attacks other fruits in Côte-d'Ivoire. In order to bring up to date the parasitic card of the fruit flies and to count some plants hosts associated with this species, the trapping technique of fruit flies was used and applied in three agro ecological areas (South, Center and North zones). Also various fruits with our range are collected then dissected. The emerged adult flies are identified and the plants hosts are listed. On the whole, 23 species were identified with a large presence of the new species B. invadens as well in the traps (91,6 %) as in the fruitscollected (69 %). The various plants from where are emerged B. invadens are detected andclassified according to the botanical families. Thus a thorough knowledge on biology,ecology and plants hosts of this species, would be necessary for a durable control at theregional and world scale.